1972
DOI: 10.1111/j.1532-5415.1972.tb00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulocytic Leukemia Associated with Myxedema Thyroiditis and Myasthenia Gravis

Abstract: A case of myxedema associated with Hashimoto's thyroiditis, myasthenia gravis, and granulocytic leukemia is described. The patient had the classical symptoms and signs of hypothyroidism. Profound myopathy, ptosis, and bulbar signs suggested myasthenia gravis and the diagnosis was confirmed by an anticholinesterase test. Treatment with cholinesterase inhibitors was ineffective and ACTH was given for increasing bulbar signs and ventilatory failure. Severe pneumonia supervened and was thought t o be the cause of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1975
1975
1993
1993

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In reviewing the literature we found 5 additional reports of lympho mas associated with MG [5,7,26,[28][29][30]. The case of reticulum cell sarcoma in a myasthenic patient reported here increases to 10 the total number of lymphoreticular malignancies reported in these patients.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In reviewing the literature we found 5 additional reports of lympho mas associated with MG [5,7,26,[28][29][30]. The case of reticulum cell sarcoma in a myasthenic patient reported here increases to 10 the total number of lymphoreticular malignancies reported in these patients.…”
Section: Discussionmentioning
confidence: 90%
“…It is mainly responsible for cellular immunity but has a definite effect on humoral immunity as well [10,11,13,25,34], Abnormal function of the thymus may cause immune deficiency states or cellular-humoral im munologic imbalance. These conditions are thought to influence the ap pearance of both malignancy and autoimmune diseases [8,10,12,23,[30][31][32], G atti and G ood [8| demonstrated that the occurrence of malig nancy, especially of the lymphoreticular system, is 10,000 times higher in patients with immune deficiency than in an age and sex-matched con trol group. Lymphomas occur in a very high rate in patients with renal transplants while on immunosuppressive therapy [12].…”
Section: Discussionmentioning
confidence: 99%